2014
DOI: 10.1111/gcbb.12178
|View full text |Cite
|
Sign up to set email alerts
|

Balance between climate change mitigation benefits and land use impacts of bioenergy: conservation implications for European birds

Abstract: Both climate change and habitat modification exert serious pressure on biodiversity. Although climate change mitigation has been identified as an important strategy for biodiversity conservation, bioenergy remains a controversial mitigation action due to its potential negative ecological and socio-economic impacts which arise through habitat modification by land-use change. While the debate continues, the separate or simultaneous impacts of both climate change and bioenergy on biodiversity have not yet been co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
(82 reference statements)
0
9
0
Order By: Relevance
“…Climate change mitigation strategies include important modifications of the land surface such as the increased prevalence of biofuel crops. This mitigation action may pose some conflicts between important areas for biodiversity conservation and bioenergy production (Alkemade et al, 2009;Fletcher et al, 2011;Meller et al, 2015). In integrated assessment models or other global land-use models, such interactions are often restricted to impacts of climate change on crop productivity and shifts in potential production areas.…”
Section: Where Biodiversity Scenarios Lack Credibilitymentioning
confidence: 99%
“…Climate change mitigation strategies include important modifications of the land surface such as the increased prevalence of biofuel crops. This mitigation action may pose some conflicts between important areas for biodiversity conservation and bioenergy production (Alkemade et al, 2009;Fletcher et al, 2011;Meller et al, 2015). In integrated assessment models or other global land-use models, such interactions are often restricted to impacts of climate change on crop productivity and shifts in potential production areas.…”
Section: Where Biodiversity Scenarios Lack Credibilitymentioning
confidence: 99%
“…A SWOT analysis tool is applied to access the opportunities, challenges, and constraints for MSW biomass as feedstock for generation of biofuels, with future development, setting priority areas for future actions. The main challenges and the opportunities are presented in Table as a SWOT analysis .…”
Section: Challenges In Biofuels Bioenergymentioning
confidence: 99%
“…Johansson et al (2016) indeed found potentially negative effects on already rare species, and de Jong & Dahlberg (2017) points out that high levels of stump extraction will likely affect species of conservation interest. At the same time, reductions of these and other species due to a warming climate may be even more severe (Ellis, 2013;Meller et al, 2015).…”
Section: Stump Harvest As a Potential Threat To Lichen Metapopulationsmentioning
confidence: 99%